2018
DOI: 10.1111/pbi.12867
|View full text |Cite
|
Sign up to set email alerts
|

Homoeologous exchange is a major cause of gene presence/absence variation in the amphidiploid Brassica napus

Abstract: SummaryHomoeologous exchanges (HEs) have been shown to generate novel gene combinations and phenotypes in a range of polyploid species. Gene presence/absence variation (PAV) is also a major contributor to genetic diversity. In this study, we show that there is an association between these two events, particularly in recent Brassica napus synthetic accessions, and that these represent a novel source of genetic diversity, which can be captured for the improvement of this important crop species. By assembling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
249
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(272 citation statements)
references
References 59 publications
(88 reference statements)
9
249
1
Order By: Relevance
“…In this study, the synthetic lines were shown to exhibit more RGAs than non‐synthetic lines, whereas non‐synthetics lines have lost more RGAs, making them an interesting model to study the impact of polyploidization on genome structure, disease resistance genes and their potential associated with agronomic traits. Greater genetic diversity in synthetic B. napus lines compared with non‐synthetic lines has previously been reported (Golicz et al ., 2016b; Hurgobin et al ., ; Li et al ., ). This difference has been attributed to the incorporation of novel alleles from diverse progenitor genomes and highlights the potential of using synthetic B. napus accessions as a source of novel genetic structural variation for breeding improved varieties (Hurgobin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, the synthetic lines were shown to exhibit more RGAs than non‐synthetic lines, whereas non‐synthetics lines have lost more RGAs, making them an interesting model to study the impact of polyploidization on genome structure, disease resistance genes and their potential associated with agronomic traits. Greater genetic diversity in synthetic B. napus lines compared with non‐synthetic lines has previously been reported (Golicz et al ., 2016b; Hurgobin et al ., ; Li et al ., ). This difference has been attributed to the incorporation of novel alleles from diverse progenitor genomes and highlights the potential of using synthetic B. napus accessions as a source of novel genetic structural variation for breeding improved varieties (Hurgobin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Greater genetic diversity in synthetic B. napus lines compared with non‐synthetic lines has previously been reported (Golicz et al ., 2016b; Hurgobin et al ., ; Li et al ., ). This difference has been attributed to the incorporation of novel alleles from diverse progenitor genomes and highlights the potential of using synthetic B. napus accessions as a source of novel genetic structural variation for breeding improved varieties (Hurgobin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recently developed pangenome of B. napus revealed high gene presence/absence variation among diverse cultivars as a result of HEs involving genes encoding important agronomic traits, including flowering time, disease resistance and chemical defenses (Hurgobin et al, 2017). HEs have also been shown to impact the expression abundance of a homoeolog proportional to the gene copy number (Lloyd et al, 2018).…”
Section: Subgenome Biases In Homoeologous Exchangesmentioning
confidence: 99%
“…Based on the results described above, the inference is that homologous exchange events occurred between the B and A/C genomes. In addition, brand‐new variation could be generated during the change from hexaploid (AABBCC) to tetraploid (AACC) because of chromosomal breakage or fusion, autosyndetic chromosome rearrangement, homologous exchange and retrotransposon activation as reported in previous studies of resynthesized B. napus (Hurgobin et al ., ; Xiong et al ., ; Zou et al ., , ). Rich new alleles and frequent deletion and duplication events were demonstrated in the inbred lines from the A r and C c polymorphism subpopulations (Xiao et al ., ; Zou et al ., , ).…”
Section: Discussionmentioning
confidence: 99%